Aloe-emodin exhibits growth-suppressive effects on androgen-independent human prostate cancer DU145 cells via inhibiting the Wnt/β-catenin signaling pathway: an in vitro and in silico study - Hussain, Talib; Alafnan, Ahmed; Almazni, Ibrahim Abdullah; Helmi, Nawal; Moin, Afrasim; Baeissa, Hanadi M.; Awadelkareem, Amir Mahgoub; Elkhalifa, AbdElmoneim O.; Bakhsh, Tahani; Alzahrani, Abdulrahman; Alghamdi, Rashed Mohammed; Khalid, Mohammad; et al. (Frontiers in Pharmacology, 2024)
At molecular level, several developmental signaling pathways, such as Wnt/β-catenin, have been associated with initiation and subsequent progression of prostate carcinomas. The present report elucidated the anti-cancerous attributes of an anthraquinone, Aloe-emodin (AE), against androgen-independent human prostate cancer DU145 cells. The cytotoxicity profiling of AE showed that it exerted significant cytotoxic effects and increased lactose dehydrogenase levels in DU145 cells (p<0.01 and p<0.001). AE also induced considerable Reactive Oxygen Species (ROS) mediated oxidative stress, which escalated at higher AE concentrations of 20 and 25 μM. AE also efficiently instigated nuclear fragmentation and condensation concomitantly, followed by activation of caspase-3 and -9 within DU145 cells. AE further reduced the viability of mitochondria with increased cytosolic cytochrome-c levels (p<0.01 and p<0.001) in DU145 cells. Importantly, AE exposure was also correlated with reduced Wnt-2 and β-catenin mRNA levels along with their target genes, including cyclinD1 and c-myc. Furthermore, the molecular mechanism of AE was evaluated by performing molecular docking studies with Wnt2 and βcatenin. Evidently, AE exhibited good binding energy scores towards Wnt2 and β-catenin comparable with their respective standards, CCT036477 (Wnt2 inhibitor) and FH535 (βcatenin inhibitor). Thus, it may be considered that AE was competent in exerting anti-growth effects against DU145 androgen-independent prostate cancer cells plausibly by modulating the expression of Wnt/β-catenin signaling.